Fertigation Effect of Distillery Effluent on Agronomical Practices of Trigonella foenum-graecum L. (Fenugreek) - Kumar, V.; Chopra, A.K. (Our Nature, 2011)
The present study was conducted to asses the fertigation effect of distillery effluent as agro-based biofertigant. Different fertigant doses of Distillery effluent (DE) such as 5, 10, 25, 50, 75 and 100% were used for fertigation of Trigonella foenum-graecum along with control bore well water (BWW). The study revealed that the fertigant, rich in plant nutrients, affected the agronomical characteristics of T. foenum-graecum (Pusa early bunching) and physico-chemical characteristics of the soil as well. On irrigation of soil with different effluents up to 90 days of harvesting, there was a significant effect on moisture content (P<0.01), EC, pH, Cl-, TOC, HCO3-, CO3-2, Na+, K+, Ca2+, Mg2+, Fe2+, TKN, NO32-, PO43- and SO42- (P<0.001) and insignificant effect on WHC and bulk density (P>0.05). There was no significant change in the soil texture. Among various concentrations of DE, irrigation with 100% DE decreased pH (16.66%) and increased moisture content (30.82%), EC (84.13%), Cl- (292.37%), TOC (4311.61%), HCO3- (27.76%), CO3-2 (32.63%), Na+ (273%), K+ (31.59%), Ca2+ (729.76%), Mg2+ (740.47%), Fe2+ (301.90%), TKN (1723.32%), NO32- (98.02%), PO43- (337.79%) and SO42- (77.78%). The agronomical parameters such as shoot length, root length, number of roots, root nodule, number of leaves, flowers, pods, pod length, dry weight, chlorophyll content, leaf area index (LAI), crop yield and harvest index (HI) of T. foenum-graecum were recorded to be in increasing order at low concentrations of DE i.e., 5 to 50% and in decreasing order at high concentrations of DE i.e., 75 to 100% as compared to control. Stimulation was observed in seed emergence period and shoot length, root length, number of leaves and biomass with the increase in effluent concentration in early seedling growth period. DOI: 10.3126/on.v8i1.4312